Genetic diversity of Anopheles triannulatus s.l. (Diptera:Culicidae) from northwestern and southeastern Colombia (2012)
ABSTRACT : Anopheles triannulatuss.l. is a species complex, however in Colombia its taxonomic status is unclear. Thisstudy was conducted to understand the level of genetic differentiation or population structure of specimens ofAn.triannulatuss.l. from northwestern and southeastern Colombia. Cytochrome oxidase subunit I (COI) and internaltranscribed spacer (ITS2) sequence analyses suggested high genetic differentiation between the NW and SE populations.A TCS network and Bayesian inference analysis based on 814 bp ofCOIshowed two main groups: group I includedsamples from the NW and group II samples from the SE. Two main ITS2-polymerase chain reaction-restriction fragmentlength polymorphism (PCR-RFLP) patterns were found. Pattern I is present in both the NW and SE, and pattern II isfound in the SE specimens. To further elucidate the taxonomic status ofAn. triannulatuss.l. in Colombia and how theseCOIlineages are related to the Triannulatus Complex species, the evaluation of immature stages, male genitalia, andadditional mitochondrial and nuclear markers will be needed.